2022
DOI: 10.1186/s12958-022-01005-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TSH on oocyte maturation of PCOS patients with normal thyroid function in IVF

Abstract: Background The serum TSH level of PCOS patients was higher than that of the general female population. For patients with thyroid dysfunction, the abnormal TSH level is negatively related to the outcomes of assisted reproductive technology, but for PCOS patients with normal thyroid function, the effect of TSH level on outcomes of in vitro fertilization has not been reported. In this study, PCOS patients with normal thyroid function were included in this study to evaluate the effect of TSH on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Further analysis of the data to only include studies in which a SCH diagnosis was ascertained using a TSH cutoff of ≥4 mUI/L, the SCH risk was 3.59 times higher in women with PCOS versus women without PCOS ( 18 ). Serum TSH concentration was higher in an infertile population of euthyroid women with PCOS versus euthyroid women without PCOS ( 36 ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Further analysis of the data to only include studies in which a SCH diagnosis was ascertained using a TSH cutoff of ≥4 mUI/L, the SCH risk was 3.59 times higher in women with PCOS versus women without PCOS ( 18 ). Serum TSH concentration was higher in an infertile population of euthyroid women with PCOS versus euthyroid women without PCOS ( 36 ).…”
Section: Resultsmentioning
confidence: 98%
“…Based on this, it is possible to speculate that PCOS and AIT and/or SCH may represent a phenotype with a particularly poor reproductive prognosis during the IVF cycle. Initial indirect evidence can be extracted from studies investigating the independent impact of TSH level on IVF-related outcomes in women affected by PCOS ( 36 , 184 ). A small prospective cohort study on 32 AIT-negative patients with PCOS and a serum TSH level of 0.4−4.5 mIU/L ( 184 ), showed that both serum and follicular fluid TSH levels were negatively correlated with the rate of oocyte maturation and fertilization, whereas high-quality embryo production rate was negatively correlated with serum TSH concentration only ( 184 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria are 18 ≤ age ≤ 40; BMI ≤ 28 kg/m 2 ; and infertility duration ≥ 12 months. The exclusion criteria are hydrosalpinx, adenomyosis, thyroid dysfunction, hyperprolactinemia, serious cardiovascular disease, diabetes mellitus, polycystic ovarian syndrome (PCOS), endometrial polyps, endometriosis, and hormone therapy in the preceding 3 months due to their strong influence on the success rate of IVF-ET. The treatment protocols of the original cohort have been described in detail in our previous study . A total of 340 participants were recruited in the original cohort after informed consent; 35 of them were lost to follow-up, resulting in 305 participants.…”
Section: Methodsmentioning
confidence: 99%
“…When the TSH level is abnormal, it can adversely affect the hypothalamus and the function of the hypothalamic-pituitary-thyroid axis, and, conversely, the imbalance of the gonadal axis in PCOS patients can affect the pituitary-thyroid axis. Many studies have found that PCOS patients with severe hyperandrogenism and insulin resistance also have abnormal thyroid function [ 83 ] Insulin Metabolic/Hormonal It is capable of increasing the frequency and amplitude of secretion of GnRH and LH pulses through upregulation of GnRH gene expression in hypothalamic GnRH neurons. Hyperinsulinemia, which may itself be caused by hyperandrogenism, potentiates the stimulatory effects of LH on androgen production in ovarian theca cells thus contributing to androgen-dependent anovulation, as well as inhibiting the production of SHBG [ 12 , 84 ].…”
Section: Laboratory Findingsmentioning
confidence: 99%